Studies with Bacteriophage φII. Events Following Infection of Male and Female Derivatives of Escherichia coli K-12 - Linial, Maxine (1970)
We studied the course of infection of the female-specific bacteriophage φII in male and female cells isogenic except for the presence of the substituted sex factor, F′lac. Both male and female cells are killed by φII; however, only limited phage replication occurs in male cells. Host macromolecular synthesis stops abruptly at 4 to 6 min after infection of male cells, and synthesis of phage components cannot be detected. Experiments with chloramphenicol indicate that phage deoxyribonucleic acid (DNA) penetrates into male cells, since protein synthesis after infection is required to stop synthesis of DNA in males. Phage DNA becomes membrane-associated in both female and male cells. In male cells, parental phage DNA does not dissociate from the membrane during the latent period as is the case with females, indicating a block in phage DNA replication. Isolation of nonrestricting F′lac mutations indicates involvement of a specific episome product in φII restriction.